A Culturally Affirming Shared Leadership Framework. Issue 1 (27th October 2022) - Gibson, Eva M.; Thompson, James M.; Cook Sandifer, Mariama I.; Brant-Rajahn, Sarah N.
The American School Counselor Association (ASCA) encourages school counselors to promote equity experiences for all students through leadership, advocacy, and collaboration. School counselors and school administrators (e.g., principals, assistant principals) are uniquely positioned to combine their social capital in an effort to create a positive school culture and empower students who have been historically oppressed. We acknowledge the existence of current leadership approaches applicable to the educational setting; however, the literature lacks action steps for these professionals to collaboratively utilize their leadership skills as they champion social justice. Therefore, we present a culturally affirming, shared leadership framework that may be applied within P–12 schools and school counselor and leadership educator preparation programs.